Riemann's Functional Equation is Not Valid and its Implication on the Riemann Hypothesis - Armando M. Evangelista Jr. (Zenodo, 2018)
Riemann’s “functional” equation was formulated by Riemann that supposedly extended the domain of the Riemann zeta function from the right half-plane into the entire complex plane except at z = 1. It is also the foundation upon which the Riemann Hypothesis is based:  that all the zeros of the zeta function are at  z = ½ + iy.  But the equation, as shall be shown here is not valid such that the Riemann Hypothesis crumbles on its claim.